IMPROVING HIV AIDS SURVEILLANCE SYSTEM IN GUNUNGKIDUL, INDONESIA:: FROM PAPER TO WEB-BASED INFORMATION SYSTEM (Proceedings of the International Conference on Public Health, 2017)
Despite the availability of web-based HIV/AIDS information system launched by ministry of health (MoH) in 2012, the HIV surveillance data in Gunungkidul district was still collected manually. This often led to incomplete and inaccurate HIV reports. This study aimed to improve HIV/AIDS surveillance in Gunungkidul. This was a two phases study with the first phase was evaluation of the system and followed by improvement of the HIV/AIDS surveillance system. Participants were the district health office (DHO) and public health centers (PHC) surveillance officers. Data were collected using structured interviews. We found VCT/PITC data had not been documented during 2015 in DHO and web-based information system was not used by PHCs because 77% of the surveillance officers were never been trained. In 2016, after the intervention, 77% of the PHC sent VCT/PITC data using web-based information system. Based on the evaluation findings, we trained 30 PHC officers to use web-based HIV/AIDS information system and developed instruction manual. The report showed that during 2016, the number of people tested for HIV was 1768 people including 1536 pregnant women and 19 tuberculosis patients, and 139 people were referred to advanced counseling. Use of web-based information system was able to increase the completeness of VCT/PITC data. DHO should monitor closely the implementation of web-based information system and provide supportive supervision to the PHCs.
Keywords: Surveillance System, HIV/AIDS, Web-based Information System